2021
DOI: 10.1108/ejm-06-2019-0531
|View full text |Cite
|
Sign up to set email alerts
|

Exploring engagement with health apps: the emerging importance of situational involvement and individual characteristics

Abstract: Purpose Health apps offer a potential approach to support healthier food behaviours but a lack of sufficient engagement may limit effectiveness. This study aims to use a user engagement theoretical lens to examine the factors that influence app engagement over time and may prompt disengagement. Design/methodology/approach A phenomenological exploration of the lived experience was used. Women from a lower socioeconomic background (based on the occupation and employment status of the household’s primary income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 102 publications
1
12
0
Order By: Relevance
“…This is particularly evident when consumers have a food-related health condition and when they are faced with time pressure. These results contribute to the literature on technology and healthy choices (Flaherty et al, 2017;Flaherty et al, 2021;Manika et al, 2017aManika et al, , 2017b and are in line with recent studies by Gustafson and Zeballos (2019), who also assess how a calorie counter can help consumers to make healthier food choices. However, our study diverges from their work, as it tests the calorie counter in a more complex choice task where consumers make a much larger number of food choice decisions.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is particularly evident when consumers have a food-related health condition and when they are faced with time pressure. These results contribute to the literature on technology and healthy choices (Flaherty et al, 2017;Flaherty et al, 2021;Manika et al, 2017aManika et al, , 2017b and are in line with recent studies by Gustafson and Zeballos (2019), who also assess how a calorie counter can help consumers to make healthier food choices. However, our study diverges from their work, as it tests the calorie counter in a more complex choice task where consumers make a much larger number of food choice decisions.…”
Section: Introductionsupporting
confidence: 89%
“…This research contributes to the emerging literature on the use of digital technologies to promote behaviour change in consumer choices by showing how aggregated nutritional information can change consumer choice. It enriches existing literature which has begun to examine the impact of technology on health-related behaviours (Flaherty et al, 2017;Flaherty et al, 2021;Manika et al, 2017aManika et al, , 2017b and also shows how information processing models (Moorman, 1990) can be applied in new contexts and augmented based on changes to technology. Overall, our results are partly in line with recent studies examining the impact of digital technologies in reducing consumer numeracy biases (Gustafson and Zeballos, 2019) and are strongly consistent with the literature on nutrition labelling more generally (Cowburn and Stockley, 2005;Grunert and Wills, 2007;Grunert et al, 2010;Moorman, 1990), as we find evidence that such information should be more relevant to consumers and that our results are partly contingent upon motivation to process nutritional information.…”
Section: Discussionmentioning
confidence: 72%
“…Patients may be inclined to regulate these emotions by decreasing the extent of their interaction with the intervention. Hence, the interplay between the emotional and behavioral domains of engagement within the context of technical problems could influence patterns of patient engagement with mHealth [ 68 ]. Thus, assessing the 3 domains of patient engagement may be pivotal in understanding the complexity of patient engagement with mHealth interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Marketing food content on social media encourages users to engage in a myriad of ways, including liking and sharing content with their friends (Dhaoui and Webster, 2021; Dolan et al , 2019; Drummond et al , 2020; Flaherty et al , 2021; Philp et al , 2022; Taheri et al , 2021). Recent work has demonstrated that social media ads for unhealthy food typically evoke more positive responses than healthy food – they are more likely to be recalled, recognized, viewed longer and shared (Murphy et al , 2020).…”
Section: Literature Review and Conceptual Developmentmentioning
confidence: 99%